Biodegradable Silica‐Based Nanotheranostics for Precise MRI/NIR‐II Fluorescence Imaging and Self‐Reinforcing Antitumor Therapy. Issue 10 (11th February 2021) - Zheng, Ziliang; Jia, Zhuo; Qu, Chunrong; Dai, Rong; Qin, Yufei; Rong, Shuo; Liu, Yulong; Cheng, Zhen; Zhang, Ruiping
Abstract: Multi‐modality cancer diagnosis techniques based on the second near‐infrared window fluorescence (NIR‐II FL, 1000–1700 nm) imaging have become the focus of research attention. For such multimodality probes, how to take advantage of the tumor microenvironments (TME) characteristics to better image diseases and combine efficient therapeutics to achieve theranostics is still a big challenge. Herein, a novel TME‐activated nanosystem (FMSN‐MnO2 ‐BCQ) employing degradable silica‐based nanoplatform is designed, adjusting the ratio of intratumoral hydrogen peroxide (H2 O2 )/glutathione (GSH) for magnetic resonance imaging (MRI)/NIR‐II FL imaging and self‐reinforcing chemodynamic therapy (CDT). Innovative bovine serum albumin (BSA)‐modified fusiform‐like mesoporous silica nanoparticles (FMSN) is fabricated as a carrier for NIR‐II small molecule (CQ4T) and MRI reporter MnO2 . Remarkably, the BSA modification helped to achieve the dual‐functions of high biocompatibility and enhance NIR‐II fluorescence. The FMSN‐MnO2 ‐BCQ with FMSN framework featuring a stepwise degradability in tumor interior released MnO2 and BCQ nanoparticles. Through the specific degradation of MnO2 by the TME, the produced Mn 2+ ions are effectively exerted Fenton‐like activity to generate hydroxyl radical (OH) from endogenous H2 O2 to eradicate tumor cells. More importantly, the GSH depletion due to the synergistic effect of tetrasulfide bond and MnO2 in turn induced the oxidative cytotoxicity for self‐reinforcing CDT. Abstract : In this study, a novel tumor microenvironments‐responsive sequential activation nanosystems (FMSN‐MnO2 ‐BCQ) employing degradable silica‐based nanoplatform is designed, adjusting the ratio of intratumoral H2 O2 /GSH for accurate dual‐modality magnetic resonance imaging/second near‐infrared window fluorescence imaging and self‐reinforcing chemodynamic therapy. The nanosystems integrate tandem functions in sequence, and each reaction has a high‐efficiency feature that is beneficial to the next step.